Nonlinear Relationship between Environmental Quality and Bank Risk-Taking in the MENA Region - Mashaqi, Eman; Albaity, Mohamed; Mallek, Ray Saadaoui (International Journal of Energy Economics and Policy, 2025)
This study investigated the nonlinear effects of environmental quality (EQ) on bank risk-taking in the region and the moderating influence on the EQ risk-taking nexus. The study employed generalized quadratic quantile regression techniques to unearth nuanced relationships within 154 publicly traded banks from 10 MENA region countries between 2011 and 2023. The results suggested a U-shaped relationship between bank risk-taking and environmental quality proxied by the environmental performance index EPI. This outcome indicated that initial advances in environmental quality were associated with reduced risk-taking, which may increase beyond a certain threshold. Furthermore, the moderating influence of bank size was substantial, as larger banks typically exhibited a more robust ability to manage environmental hazards without increasing their risk-taking behaviour. The implications for policy and practice are substantial, indicating that developing effective risk management strategies should consider both the size of banks and environmental improvements.